Asymmetric cyclopropanation reactions catalyzed by carbohydrate-based crown ethers. Issue 27 (5th July 2018) - Rapi, Zsolt; Nemcsok, Tamás; Grün, Alajos; Pálvölgyi, Ádám; Samu, Gyula; Hessz, Dóra; Kubinyi, Miklós; Kállay, Mihály; Keglevich, György; Bakó, Péter
Abstract: Optically active cyclopropane derivatives were prepared by a novel, simple and green approach in high enantioselectivities using monosaccharide-based chiral crown ethers as phase transfer catalysts. The crown ethers having d -glucopyranoside, d -mannopyranoside and d -altropyranoside units proved to be efficient catalyst in a few asymmetric phase transfer cyclopropanation reactions. The Michael-initiated ring closure (MIRC) reactions of diethyl bromomalonate with chalcones took place with complete diastereoselectivity and up to 99% ee. Using benzylidenemalononitrile, 2-arylidenemalononitriles, 2-benzylidene-1, 3-indandione, substituted 2-benzylidene-1, 3-indandiones, 2-arylidene-1, 3-indandiones and 2-benzylidene-1, 3-diphenyl-1, 3-propanediones enantioselectivities up to 92%, 99%, 54% 93%, 89% and 72%, respectively, were achieved, in the presence of chiral lariat ethers derived from different monosaccharides. The absolute configuration of a cyclopropane diester product was determined by a combined CD spectroscopic and theoretical study. Graphical abstract: Image 1